A child with hyperekplexia and epileptic myoclonus. Issue 4 (29th August 2018) - Wadi, Lara; Medlej, Yasser; Obeid, Makram
ABSTRACT: Hyperekplexia is a rare neurogenetic disorder characterized by startle. Accurate diagnosis of this notorious mimicker of epilepsy is important to prevent life‐threatening apnoea. We report a novel case of concomitant GLRA1 ‐related hyperkeplexia and myoclonic epilepsy. A toddler with daily paroxysms of head drops and falls presented with epileptic myoclonus on EEG, however, whole‐exome sequencing revealed hyperekplexia‐related GLRA1 mutation. The boy eventually developed spells induced by noise and surprise. All his spells remitted upon treatment with clonazepam. Paediatricians and paediatric neurologists should be aware of this possible mixed presentation in order to appropriately tailor medication regimens and treatment goals. [ Published with video sequence on www.epilepticdisorders.com ].